Effects of Aft-Body Extension Design on the Fundamental Characteristics of HWB Civil Aircraft - Yucheng Wang; Gang Liu; Guanxin Hong (Applied Sciences, 2022)
The extension of aft-body fuselage has become an important trend in the design of Hybrid Wing Body (HWB) civil aircraft due to its improved effect on flight control authority of aircraft. However, it is still unclear how efficient the extension of aft-body will be in improving flight control authority and how it affects other aspects of the flight performance of HWB. To address these problems, this paper evaluated and compared the flight performances of four HWB configurations with different aft-body lengths. A physics-based Multidiscipline Design Optimization (MDO) platform was firstly constructed, and four optimal design works were developed based on this platform, with different static margin constraints. The configurations to be studied came from the results of the four optimization design works, which presented different aft-body lengths under the influence of correspondence between static stability margins and aft-body layout. By investigating these four HWB configurations with the weight, basic takeoff and landing performance, and flight control authority, we can determine the influence of the aft-body extension design on the performances of the HWB civil aircraft and provide advice for the layout design of the HWB aircraft.